(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
In this article, the content of the round discussion on the educational technology of the primary training sessions before the convocation is carried out based on the requirements of the Regulations of the Armed Forces of the Republic of Uzbekistan, the shooting training sessions are based on the instructions and guidelines for working with training and combat weapons, most of the training sessions are educational and material. close connection with the base, specific aspects of military training